SUCEPTIBILITY OF SOME WHEAT CULTIVARS TO COMMON BUNT - A. Al-Taae (Mesopotamia Journal of Agriculture)
The results form the susceptibility estimation for five cultivars of bread wheat, Vees, Adnania1, Adnania2, IPA99 and Abo-Graib and three durum wheat cultivars, Om-Rabia, Sham1 and Sham5 against the common bunt disease indicated the durum wheat were resistant and more best from the bread wheat, therefore, Om Rabea cultivar showed a highly resistant for disease, and the infection percent was not encroach means 4.49% that's a significantly differences from the other cultivars, which follow it the sham1 cultivar significantly differences from the other cultivars too. The Vees cultivar was appeared highly sensitive to disease and infected percent which became 71.59%, while Abo-Grieb and IPA99 were showed 57.89 and 51.32% respectively. The durum wheat were comment a resistant against T. laevis more than T. tritici, where as the bread wheat cultivars become susceptible to each species of fungus.